AKUNTANSI PERBANKAN SYARIAH (Sebuah Kajian Teori dan Praktek Kontemporer) - Ali Mauludi AC (IQTISHADIA Jurnal Ekonomi & Perbankan Syariah, 2015)
Accounting of Shari’ah Banks is the financial accounting process from the collection of funds, distribution of funds. Every collection of funds is done by Shari’ah Banks have the accounts that are different from conventional banks. In the collection and Shari’ah Banks uses the accounts product and savings wadi'ah and savings and mudharabah deposits. In distributing and to Shari’ah Bank community uses 3 featured products  are, financing mudharabah, Musharaka and buying and selling murabahah.